2015
DOI: 10.1039/c5ra05091j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of boron nitride nanotubes functionalized with gum arabic on the differentiation of rat mesenchymal stem cells

Abstract: The use of nanostructured materials in biomedical applications has been widely investigated, in particular with the aim of using these materials to selectively carry drugs or molecules of interest to a target tissue or organ. Boron nitride nanotubes (BNNTs) functionalized with specific moieties have been demonstrated to be useful candidates for the targeted delivery of proteins, drugs and nucleic acids. We evaluated the influence of BNNTs functionalized with gum arabic on the differentiation of mesenchymal ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The cell viability was more than 80% in all the studied concentrations, indicating no adverse effects on HeLa cultures in terms of metabolic activity after the incubation time. This result is in accordance with others studies that show the good biocompatibility of BNNTs up to 200 μg/mL [ 10 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The cell viability was more than 80% in all the studied concentrations, indicating no adverse effects on HeLa cultures in terms of metabolic activity after the incubation time. This result is in accordance with others studies that show the good biocompatibility of BNNTs up to 200 μg/mL [ 10 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…Recent studies have shown that BNNTs present no apparent toxicity in the concentrations required for their good performance [ 6 ]. It has been demonstrated that BNNTs are internalized by cells [ 7 ], can efficiently deliver DNA [ 8 ], and improve the process of gene transfection [ 9 ] and the differentiation of mesenchymal stem cells [ 10 ]. Furthermore, a theoretical study by Hilder and Hill shows that BNNTs are suitable for drug encapsulation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ciofani et al reported that poly-L lysine functionalized BNNT effectively conjugates fluorescent markers (quantum dots) and targeting moieties (folic acid) thus exhibiting good dispersing ability and cytocompatibility [33][34][35] . Li et al proved that BNNT enhances the differentiation of mesenchymal stem cells into osteoblasts 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it was reported that BNNTs were able to enhance the osteogenesis of MSCs, which showed potential in bone regeneration in orthopaedic applications [52]. Ferreira et al [60] incubated GA-BNNTs in MSCs to investigate the cytocompatibility. The cell viability and proliferation were not affected, up to 20 µg•mL −1 of GA-BNNTs [60].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%